MODEL PEMBELAJARAN INQUIRY TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Isep Periyana; Lucy Asri Purwasi; Sujarwo (Jurnal Binagogik, 2024)
This research aims to determine students' conceptual understanding abilities after applyingthe inquiry model to class V data processing material. This research method uses a quasiexperiment with a population of class V students at SD Negeri 3 Lubuklinggau for the2023/2024 academic year, totaling 24 students. The sample selection technique is saturatedsampling. The data collection method for this research is a test in the form of a descriptionof 6 questions. Data analysis techniques for research results mean the post-test conceptualunderstanding score is 78.82 in the good category. Data analysis using the Z-Test is basedon the results of the final test with a significant level of α = 0.05 and the results of theanalysis of the hypothesis test, namely zcount (4.08) > ztable (1.64), so it can be concludedthat the understanding of mathematics concepts of fifth grade students at state elementaryschools 3 Lubuklinggau after implementing the guided inquiry learning model wassignificantly in the good category (µ>70).